Integrating Enrichment, Reduction, and Oxidation Sites in One System for Artificial Photosynthetic Diluted CO2 Reduction - Yang, Yan; Zhang, Hong‐Yu; Wang, Ya; Shao, Lu‐Hua; Fang, Liang; Dong, Hong; Lu, Meng; Dong, Long‐Zhang; Lan, Ya‐Qian; Zhang, Feng‐Ming (Advanced materials (Weinheim), 2023)
Artificial photosynthetic diluted CO2 reduction directly driven by natural sunlight is a challenging, but promising way to realize carbon‐resources recycling utilization. Herein, a three‐in‐one photocatalytic system of CO2 enrichment, CO2 reduction and H2O oxidation sites is designed for diluted CO2 reduction. A Zn‐Salen‐based covalent organic framework (Zn‐S‐COF) with oxidation and reductive sites is synthesized; then, ionic liquids (ILs) are loaded into the pores. As a result, [Emim]BF4@Zn‐S‐COF shows a visible‐light‐driven CO2‐to‐CO conversion rate of 105.88 µmol g−1 h−1 under diluted CO2 (15%) atmosphere, even superior than most photocatalysts in high concentrations CO2. Moreover, natural sunlight driven diluted CO2 reduction rate also reaches 126.51 µmol g−1 in 5 h. Further experiments and theoretical calculations reveal that the triazine ring in the Zn‐S‐COF promotes the activity of H2O oxidation and CO2 reduction sites, and the loaded ILs provide an enriched CO2 atmosphere, realizing the efficient photocatalytic activity in diluted CO2 reduction. A three‐in‐one photocatalytic system of CO2 enrichment, CO2 reduction, and H2O oxidation sites is designed for diluted CO2 reduction, and the [Emim]BF4@Zn‐Salen‐COF shows excellent visible‐light‐driven and natural‐sunlight‐driven CO2‐to‐CO conversion activity under diluted CO2 (15%) atmosphere.